Informe de pasantía en la cámara de comercio e industria colombo chilena (2020)
Currently, as a degree requirement to opt for the Professional Degree in International Trade at the Antonio Nariño University, the Business Practice modality is available, which allows its students to have a different field than the academic one in which you can only learn through experience, an experience that puts into practice what has been theoretically studied and its results are denoted in the labor field. With the above, the business practice was carried out in the Chilean Colombian Chamber of Commerce and Industry, which in this document evidences the functions performed in the Colombian commercial area, becoming agents due to the support in the efforts made in order to achieve approaches commercial or alliances between affiliated companies. Trough data collection, market studies, and writing reports, calls were made and prospecting contacts were made to new markets, thus accompanying business missions because many companies are unaware of the services and benefits provided by this entity in the development and growth of your organization.